WHO’S AWARE CLASSIFICATION AS A TOOL OF ANTI-MICROBIAL STEWARDSHIP PROGRAM: A TEACHING HOSPITAL-BASED STUDY - TAUSEEF NAZIR; MAJID FAROOQ; SEMIRA IMRAN; NASEER MIR; MEHREEN IMRAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to evaluate the antimicrobial utilization pattern and compare it with the World Health Organization’s (WHO’s) access, watch, and reserve (AWaRe) framework for the effective implementation of anti-microbial stewardship program (ASP) for tackling antimicrobial resistance (AMR). Methods: This was a prospective, observational study conducted by the Department of Pharmacology in association with the Department of Orthopedics, Sher-I-Kashmir Institute of Medical Sciences. Data pertaining to all 208 patients was obtained from the wards of Medical College and Hospital, Bemina, Srinagar, India, for 6 months. Results: The total number of patients in our study was 208, among them 74 patients received anti-microbial agents (AMAs) from the WHO’s access category whereas 134 were prescribed AMAs from the watch category. The percentage of AWaRe AMAs usage in comparison to the WHO criteria was 35.5% for the access list (WHO optimal value ≥60%), whereas it was 64.4% for the watch list (WHO optimal value ≤40%). Conclusion: The government of India has no doubt taken a few steps to address this issue but a proactive approach is the need of the hour to minimize AMR saving precious lives and reduce global economic burden, further prescribing doctors should undergo periodic training to update their knowledge. Standard guidelines as developed by AIIMS and WHO should be followed across all the health facilities in India.